CAPITAL, INNOVATION, AND FINANCIAL MANAGEMENT AS DETERMINANTS OF MSME PERFORMANCE IN TLOGOMAS VILLAGE - Dwi Susanti, Rizki Aprilia; Dewi Novitawati, Retno Ayu (Referensi : Jurnal Ilmu Manajemen dan Akuntansi, 2024)
This study is a quantitative research aiming to analyze how capital, innovation, and financial management influence the performance of MSMEs in Tlogomas Village. The sample consists of 35 respondents, representing MSME actors in the area. Data were collected through questionnaires completed by these MSME actors. The data were analyzed using multiple linear regression analysis.Based on the t-test results, it was concluded that the capital variable (X1) does not significantly affect MSME performance in Tlogomas Village. Meanwhile, the innovation variable (X2) has a significant effect on MSME performance. The financial management variable (X3) also has a significant effect on MSME performance, with a significance level of 0.003 0.05 and a t-value of 2.008. The F-test results indicate an F-value of 1.523 with a significance level of 0.228 0.05, suggesting that the variables of capital, innovation, and financial management have a simultaneous influence on MSME performance in Tlogomas Village.